2008
DOI: 10.1590/s0103-49792008000300010
|View full text |Cite
|
Sign up to set email alerts
|

trabalho infantil no brasil contemporâneo

Abstract: Este trabalho analisa o panorama atual do trabalho infantil na sociedade brasileira, abordando a sua origem, trajetória recente, efeitos sobre as crianças e adolescentes e políticas que vêm sendo desenvolvidas para combatê-lo. Baseando-se em tabulações especiais da PNAD de 2006, ele mostra a dimensão do fenômeno e como a atividade precoce se diferencia conforme a idade, o sexo, a residência rural e urbana e as grandes regiões, assinalando suas condições de atividade e seus impactos perversos sobre a educação e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1
23

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 1 publication
(1 reference statement)
0
6
1
23
Order By: Relevance
“…The presence of female street vendors evidenced by the present study is in disagreement with studies [23][24][25][26] that reported that this kind of work is essentially done by males. In this context, the presence and prevalence of girls selling quail eggs may be justified by the relative ease of the job.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The presence of female street vendors evidenced by the present study is in disagreement with studies [23][24][25][26] that reported that this kind of work is essentially done by males. In this context, the presence and prevalence of girls selling quail eggs may be justified by the relative ease of the job.…”
Section: Discussioncontrasting
confidence: 99%
“…In this sense, many risks may be present in their daily routine, such as injuries, long walks in the sun, dehydration, and sexual and/or moral harassment, as pointed out by Carvalho 25 and Audu et al 30 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apesar da evidência de frequência à escola, a identificação de atraso ou mesmo de abandono escolar expressa consequências bem estabelecidas na literatura entre as principais consequências do trabalho infantil 24,25 , o que contribui marcadamente para manter o ciclo de pobreza nas famílias.…”
Section: Características Dos Vendedores E Do Trabalhounclassified
“…deslocamento: condição que propicia a ocorrência de acidentes e queimaduras, conforme relatos obtidos em campo. Essa descrição remete a preocupações de natureza epidemiológica, tendo em vista a ocorrência de injúrias relacionadas ao trabalho de crianças e adolescentes relatadas no Brasil 25 e na América Latina 27 .…”
Section: Características Dos Vendedores E Do Trabalhounclassified